Evaluasi Potensi Untuk Pengembangan Destinasi Coban Putri Berdasarkan Daya Tarik Wisata - Siregar, Fauzi Sheva Hamzah; Wirahayu, Yuswanti Ariani; Wagistina, Satti; Irawan, Listyo Yudha (JURNAL DESTINASI PARIWISATA, 2024)
Research evaluating the potential for developing the Coban Putri destination based on tourist attractions aims to (1) determine the potential for Coban Putri tourist attractions, and (2) determine the direction of developing the potential for Coban Putri tourist attractions. This research uses a survey method in the form of direct field observations and interviews with managers and visitors as well as analysis of secondary data obtained from government agencies and institutions in Batu City. The analysis technique uses descriptive qualitative by describing and presenting information from the data obtained. The results of this research show that there is a picture of natural tourism potential and special interests that are attractive in tourist attractions. The development of 4A tourist attractions, namely, attractions, is demonstrated by the existence of various interesting photo spots as well as special interest attractions such as off-road, flying fox, camping, paint ball, outbound, rock climbing which should be done every day, not just during the day. weekends. Apart from additional attractions that need to be upgraded, the management also has to make improvements to several neglected photo spots. Accessibility with results showing developments regarding road conditions, parking lots, road signage that must be repaired. The results of the facilities (amenities) show that development is still not good because there are several facilities that cannot be used by tourists. Additional services (ancillary service) with the results showing the number of officers, promotions and tour package offers must be improved, but to support additional services there are (hospitals, pharmacies, accommodation, gas stations, ATM machines and souvenir shops) which are complete and close to Coban Purtri tourist attraction. Keywords: Evaluation, Development, Attraction